Travel Behaviour Response to Major Transport System Disruptions Implications for Smarter Resilience Planning - Marsden, Greg (OECD Publishing, 2016)
The current focus of transportation policy around disruptive events is to adopt an engineering resilience-oriented approach, which focuses on returning assets to good workable order as soon as possible. This will remain critically important in the future to reduce the scale and severity of disruptive events which are likely to become more commonplace in many locations due to climate change. It is, however, only one part of ensuring that such events have more limited impacts on society and the economy. A broader consideration of societal resilience and responses outside the transport sector is needed. People travel in order to take part in activities (work, education, caring and so on), and a smarter resilience response requires us to better understand these activity patterns and intervene accordingly. There is significant adaptive capacity within society that could be better harnessed to reduce the impacts of disruptive events.
Keywords: Transport